(Dis)comfort, judgement and solidarity: affective politics of academic publishing in development studies. Issue 3 (21st March 2022) - Alburo-Cañete, Kaira Zoe; Banerjee, Shonali Ayesha; Hak, Sochanny; Jakimow, Tanya; Ngin, Chanrith; Sadjad, Mahardhika Sjamsoe'oed; Schech, Susanne; Underhill-Sem, Yvonne; Wu, Joyce
Abstract: The publication of a controversial article in Third World Quarterly and the consequent unveiling and critical questioning of journal practices continue to engender strong negative feelings for many scholars. At a critical juncture within the publication process of this collection, we faced an ethical dilemma regarding how to maintain political and ethical commitments while manoeuvring within a sometimes hostile academic environment. Here we examine the dilemma and its resolutions to reflect on configurations of power in academia. Through the lenses of (dis)comfort, judgement and solidarity, we examine the affective intensities that shaped our individual and collective decisions. Reflections on the process reveal the need to attend to how affects shape the resolution of shared ethical dilemmas in ways that reinforce structural (dis)advantages. We argue that 'comfort', achieved through solidarities, allows for the navigation of the ethical-political in ways open to multiple possibilities. Decolonial practice should attend to affective practices that privilege some claims over others and limit the capacity of future scholars to shape the ethical terrain of development studies.